2021
DOI: 10.46989/001c.31303
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the physiological responses to heat stress of juvenile and adult starry flounder (Platichthys stellatus)

Abstract: Water temperature is the most important factor in fish farming as changes in water temperature cause physiological stress in fish. There have been few studies on physiological responses to high temperatures, which vary with aging. This study investigated the responses of juvenile and adult Platichthys stellatus to heat stress. Plasma cortisol, glucose, lactate, and lysozyme levels, antioxidant enzyme activities, and expression of heat shock proteins 70 and 90 (HSP70 and HSP90) of P. stellatus were determined a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 88 publications
(102 reference statements)
1
2
1
Order By: Relevance
“…This indicates that size has little effect on the expression of HSP70 mRNA in spotted seabass, which is different from the results observed in the starry flounder Platichthys stellatus and rainbow trout Oncorhynchus mykiss, which may be related to species differences and sampling organization [49,54]. At the same time, we observed that the expression of HSP90 mRNA in small spotted seabass was significantly higher than that in large spotted seabass, indicating that the expression of HSP90 mRNA varies with size, which is consistent with the results observed in starry flounder Platichthys stellatus [49]. In general, we observed a high level of constitutive HSPs (HSP90, HSP90) expression in the liver of small spotted seabass.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…This indicates that size has little effect on the expression of HSP70 mRNA in spotted seabass, which is different from the results observed in the starry flounder Platichthys stellatus and rainbow trout Oncorhynchus mykiss, which may be related to species differences and sampling organization [49,54]. At the same time, we observed that the expression of HSP90 mRNA in small spotted seabass was significantly higher than that in large spotted seabass, indicating that the expression of HSP90 mRNA varies with size, which is consistent with the results observed in starry flounder Platichthys stellatus [49]. In general, we observed a high level of constitutive HSPs (HSP90, HSP90) expression in the liver of small spotted seabass.…”
Section: Discussioncontrasting
confidence: 94%
“…This implies that stress levels were higher in large spotted seabass than in small spotted seabass at the same temperatures, causing its energy consumption to be faster. Similar results were observed in starry flounder Platichthys stellatus under heat stress conditions [49].…”
Section: Discussionsupporting
confidence: 85%
“…The upregulated expression levels of HSP70 and HSP90AB1 in the liver of T. ovatus are helpful for the refolding of misfolded proteins in cells, maintaining protein homeostasis and regular physiological functions, and minimizing damage to the fish body during heat stress. Consistent with this result, as the water temperature increased, the expression levels of HSP70 and HSP90 were also enhanced in brown trout ( Salmo trutta fario ) skin tissue [ 60 ], grass carp ( Ctenopharyngodon idellus ) liver tissue [ 61 ], spotted sea bass ( Lateolabrax maculatus ) liver and muscle tissue [ 62 ], O. mykiss head kidney and brain tissue [ 63 , 64 ], starry flounder ( Platichthys stellatus ) kidney tissue [ 65 ], and lake whitefish ( Coregonus clupeaformis ) liver tissue [ 66 ]. This regulation helps maintain intracellular protein homeostasis, minimizing the damage caused by high-temperature stress to the body.…”
Section: Discussionmentioning
confidence: 79%
“…For instance, heat stress is one of the contributing factors to reduced milk yields and quality, decreased meat production, and fertility issues in farm animals [ 3 ]. Moreover, thermal stress also induces physiological, behavioral, and production changes in poultry [ 4 ], as well as alterations in growth rate, oxidative stress, and immune response in fish [ 5 ]. As a result, animal stress has led to significant drawbacks in the agriculture sector and the nation’s economy.…”
Section: Introductionmentioning
confidence: 99%